2007
DOI: 10.1037/0096-3445.136.3.485
|View full text |Cite
|
Sign up to set email alerts
|

Scope of linguistic influence: Does a classifier system alter object concepts?

Abstract: Whether and to what extent conceptual structure is universal is of great importance for understanding the nature of human concepts. Two major factors that might affect concepts are language and culture. The authors investigated whether these 2 factors affect concepts of everyday objects in any significant ways. Specifically, they tested (a) whether the system of grammatical categorization by classifiers influenced the conceptual structure of speakers of classifier languages, and (b) whether Westerners organize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
69
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 56 publications
(99 reference statements)
11
69
4
Order By: Relevance
“…Since Mandarin speakers use classifier information to direct overt attention, as shown in the (almost identical) Experiment 1, the absence of the critical attention shift in Experiment 2 is not a procedural artifact. The findings of Experiment 2 are consistent with a priming study reported by Saalbach and Imai (2007;see Gao and Malt, 2009). These researchers found that reaction times were not facilitated by providing a written prime from the same classifier category as the name of a visually-depicted target.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Since Mandarin speakers use classifier information to direct overt attention, as shown in the (almost identical) Experiment 1, the absence of the critical attention shift in Experiment 2 is not a procedural artifact. The findings of Experiment 2 are consistent with a priming study reported by Saalbach and Imai (2007;see Gao and Malt, 2009). These researchers found that reaction times were not facilitated by providing a written prime from the same classifier category as the name of a visually-depicted target.…”
Section: Discussionsupporting
confidence: 82%
“…Whereas research using offline measures has found a strong influence of Mandarin classifiers on conceptualization, research using more online (or implicit) measures (e.g., Saalbach and Imai, 2007;Gao and Malt, 2009; Experiment 4) has revealed either no classifier effects or only modest ones. Saalbach and Imai (2007), for example, conducted a priming experiment with printed word primes and picture targets.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To conclude, simply demonstrating a cross-linguistic difference (or lack of it) due to a given linguistic category and arguing for (or against) the Whorfian hypothesis is no longer satisfactory to fully understand the relation between language and thought (Imai & Masuda, 2013;Imai & Mazuka, 2007;Imai & Saalbach, 2010;Saalbach & Imai, 2007. The present research not only showed that grammatical gender affects German speakers' reasoning about sex-specific properties but also specified how the influence arises and the scope of the influence.…”
Section: Implications For Research On the Relation Between Language Amentioning
confidence: 99%